1967
DOI: 10.1071/ph670507
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Dislocations and Coercivity in Fine Grained Magnetite

Abstract: SummaryInteraction of the stress field of a favourably oriented edge dislocation with the magnetostriction in a ferromagnetic domain wall in magnetite causes the dislocation to act as a potential well for the domain wall. The coercivity of 20 pm. grains, in which the domain structure is considered to be particularly simple, can be explained on this basis if the dislocations are arranged so that the effects of several of them are additive. The required density of edge dislocations is 109 cm-2, which is entirely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…Vicena (1954Vicena ( , 1955 calculated the force exerted by a dislocation on a domain wall and used this calculation to develop a satisfactory model for the coercive force of iron and nickel. Stacey and Wise (1967) used a similar approach to account for the coercive force of small magnetite particles. Shive (in press) showed that the variation of saturation IRM and strong field TRM with dislocation density in nickel could be explained by a domain wall pinning model.…”
Section: Introductionmentioning
confidence: 99%
“…Vicena (1954Vicena ( , 1955 calculated the force exerted by a dislocation on a domain wall and used this calculation to develop a satisfactory model for the coercive force of iron and nickel. Stacey and Wise (1967) used a similar approach to account for the coercive force of small magnetite particles. Shive (in press) showed that the variation of saturation IRM and strong field TRM with dislocation density in nickel could be explained by a domain wall pinning model.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely then, that stress is responsible for the high coercivities associated with magnetite-ilmenite lamellae. The division of magnetite by ilmenite lamellae into elongate single domain regions with high shape anisotropy, as proposed by Strangway et al, (1968), is clearly the best explanation.…”
Section: Discussion-magnetic Effectsmentioning
confidence: 78%
“…Accordingly, the parameters employed are those of pure magnetite and pure ilmenite. Strangway et al (1968) show several excellent microphotographs of these ilmenite lamellae. The lamellae are quite persistent, often forming {111} sandwiches of magnetite which can be traced completely across crystals 50-75u thick.…”
Section: Lamella Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aithough experimental results indicate that defects play an imp6rlant role in producing stable magnetization in some magnetic minerals common to rocks (e.g., Hodych, 1982), most detailed theoretical calculhtions suggest there should be only minor increases in stability due to defects (e.g., Stacey and Wise, 1967). In spite of such uncertainties, there are some observational data suggesting that (ii) is not responsible for some of the observed overprinting mentioned in the last section.…”
Section: Mechanism (Ii) Is More Difficult To •Valuate Because Of Uncementioning
confidence: 89%